Comparative phylogeography of African fruit bats (Chiroptera, Pteropodidae) provide new insights into the outbreak of Ebola virus disease in West Africa, 2014–2016 - (:unkn) unknown (My University, 2016)
Both Ebolavirus and Marburgvirus were detected in several fruit bat species of the family Pteropodidae, suggesting that this taxon plays a key role in the life cycle of filoviruses. After four decades of Zaire Ebolavirus (ZEBOV) outbreaks in Central Africa, the virus was detected for the first time in West Africa in 2014. To better understand the role of fruit bats as potential reservoirs and circulating hosts between Central and West Africa, we examine here the phylogeny and comparative phylogeography of Pteropodidae. Our phylogenetic results confirm the existence of four independent lineages of African fruit bats: the genera Eidolon and Rousettus, and the tribes Epomophorini and Scotonycterini, and indicate that the three species suspected to represent ZEBOV reservoir hosts (Epomops franqueti, Hypsignathus monstrosus, and Myonycteris torquata) belong to an African clade that diversified rapidly around 8–7 Mya. To test for phylogeographic structure and for recent gene flow from Central to West Africa, we analysed the nucleotide variation of 675 cytochrome b gene (Cytb) sequences, representing eight fruit bat species collected in 48 geographic localities. Within Epomophorina, our mitochondrial data do not support the monophyly of two genera (Epomops and Epomophorus) and four species (Epomophorus gambianus, Epomops franqueti, Epomops buettikoferi, and Micropteropus pusillus). In Epomops, however, we found two geographic haplogroups corresponding to the Congo Basin and Upper Guinea forests, respectively. By contrast, we found no genetic differentiation between Central and West African populations for all species known to make seasonal movements, Eidolon helvum, E. gambianus, H. monstrosus, M. pusillus, Nanonycteris veldkampii, and Rousettus aegyptiacus. Our results suggest that only three fruit bat species were able to disperse directly ZEBOV from the Congo Basin to Upper Guinea: E. helvum, H. monstrosus, and R. aegyptiacus.
Keywords: African Research